Can cold water immersion enhance recovery in elite Olympic weightlifters? An individualized perspective - Schimpchen, J.; Wagner, M.; Ferrauti, A.; Kellmann, M.; Pfeiffer, M.; Meyer, T. (The Journal of Strength and Conditioning Research, 2017)
We investigated whether cold water immersion (CWI) after intensive training sessions can enhance recovery in elite Olympic weightlifters, taking into account each athlete's individual response pattern. The entire German male Olympic weightlifting national team participated in the study (n = 7), ensuring collection of data from elite athletes only. Using a randomized cross-over design, the athletes went through 2 high-intensity training microcycles consisting of 5 training sessions that were either followed by a CWI or passive recovery. Barbell speed in a snatch pull movement, blood parameters, and subjective ratings of general fatigue and recovery were assessed throughout the study. Physical performance at 2 snatch pull intensities (85% one repetition maximum [1RM]: -0.15% vs. -0.22%, p = 0.94; 90% 1RM: -0.7% vs. +1.23%, p = 0.25) did not differ significantly (condition × time). Although questionnaires revealed a significant decline in the ratings of overall recovery (p < 0.001) and a significantly higher rating of overall stress (p = 0.03) over time, no significant differences between conditions (p = 0.14; p = 0.98) could be revealed. Similarly, neither of the analyzed blood parameters changed significantly between conditions over time (creatine kinase: p = 0.53; urea: p = 0.43; cortisol: p = 0.59; testosterone: p = 0.53; testosterone:cortisol ratio: p = 0.69). In general, CWI did not prove to be an effective tool to enhance recovery in elite Olympic weightlifters over a 3-day intensive training period. However, even though the group was rather homogeneous with regard to performance, there were considerable intersubject differences in their response to CWI. It seems that athletes are best advised on a case-by-case basis.